Importance attached to sexual intercourse, orgasm, sexual satisfaction and binge eating - Pereira, Filomena (2018)
Previous research suggests a relationship between Sexual Satisfaction and Binge Eating Disorders (BED): in patients with BED the act of eating replaces sexual pleasure and is used to hide sexual desires and to escape sex (Viveiros, 2012), promoti the reduction of sexual interest and lower quality of sexual life (Esposito, 2008, 2007; Adolfsson, 2004).Is there a statistically significant correlation between sexual satisfaction, BED, orgasm perception, and the importance attached to sexual intercourse? A quantitative, descriptive and correlational study, with application of the Sexual Satisfaction Index (SSI) (Pechorro et al., 2009) and the Binge Eating Scale (Freitas et al., 2001) in a sample of 218 patients (68.3% woman and 31.7% men) aged 18 to 65 years, with different categories of Body Mass Index (BMI). The data was collected in several health institutions in the center and north of Portugal.A positive and significant correlation between BED (r = 205, p < .001) and SSI was found. Sexual satisfaction establishes weak and moderate but statistically significant negative correlations with the importance attributed to sexual relations (r = -.233, p < .001) and with orgasm perception during sexual intercourse (r = -.482, p <.001). A higher level of BED corresponds to lower importance attributed to sexual relations (r = -.185, p < .001) and the lower orgasm perception during sexual relations (r = -.296, p < .001). In addition, the importance attributed to sexual relations in life and the perception of reaching orgasm showed a moderate significant correlation (r = .378, p < .001).